Fantastic beasts & where to find them - Scamander, Newt; Rowling, J. K. (Arthur A. Levine Books an imprint of Scholastic Inc.; Obscurus Books, 2015)
A description of beasts, believed by Muggles to be mythical, like the Quintaped, the Puffskein, and the Knarl.